Strategi Guru Dalam Pembelajaran PAI Terhadap Anak Intelectual Disability - Cici Indriani; Rini Rahman (An-Nuha, 2024)
This research was motivated by problems that the author found at SD N 30 Lubuk Lintah, namely: At this school, the author interviewed a teacher (PAI) who taught children with special needs with different characteristics. There are two students with special needs at SD Negeri 30 Lubuk Lintah, one boy and one girl, both of whom have intellectual disabilities and are in class V. When the learning strategies used do not achieve the learning objectives, this becomes a problem for PAI teachers. This research uses qualitative methods. The type of research chosen by the author in this research is a descriptive approach. Data collection procedures include interviews, observation, and documentation. The results of this research show that the strategies used by teachers in learning Islamic religious education at SD N 30 Lubuk Lintah can be seen from the activities: open learning, presentation of material, providing reinforcement, and closing the lesson. Teachers use conventional strategies in learning activities whereas Islamic religious teachers dominate the learning process.